Incidence and impact on prognosis of heart failure in Middle Eastern patients undergoing percutaneous coronary interventions - Hammoudeh, Ayman J; Al-Natour, Dalal; Khader, Yousef; Alhaddad, Imad A; Tabbalat, Ramzi; Al-Mousa, Eyas; Saleh, Akram (Asian Journal of Medical Sciences, 2017)
Background: Heart failure (HF) is a serious complication of percutaneous coronary intervention (PCI) that adversely impacts survival and quality of life. Aims and Objectives: We sought to study the incidence of HF in Middle Eastern patients undergoing PCI and its impact on prognosis. Materials and Methods: The first Jordanian PCI Registry was a prospective multicenter study of PCI patients who were followed for one year. Patients who developed heart failure during hospitalization had their clinical and coronary angiographic profiles and adverse outcomes compared with those in patients who did not develop HF. Results: Of 2425 patients who had PCI, 194 (8.0%) developed HF during the hospital stay. Compared with patients who did not develop HF, those who developed HF were more likely to have diabetes mellitus, prior history of myocardial infarction (MI), elevated levels of cardiac biomarkers, ST-segment elevation MI and multivessel or left anterior descending coronary artery disease (all p values<0.05). Cardiac mortality was significantly higher among patients who developed HF compared with those who did not (5.2% vs. 0.4%; p<0.0001) and at one year (11.2% vs. 1.2%; p<0.001). Multivariate analysis showed that HF during hospital stay was an independent predictor of one-year cardiac mortality (Odds ratio 6.1, 95% CI 3.3-11.1, p<0.001) . At one year, readmission rates for HF and ACS were higher among HF patients. Conclusions: Certain clinical and angiographic features were associated with higher incidence of HF among Middle Eastern patients who undergo PCI. HF was associated with higher risk of death and other adverse cardiac events during hospital stay and one year of follow up. Asian Journal of Medical Sciences Vol.8(2) 2017 20-28